Analisis Uprating terhadap Transformator di PT. PLN (Persero) ULP Panakkukang - Prambana, Saprijal; Aslam, Nur; Suryani, Suryani; Nirwana, Hafsah (MASALIQ, 2023)
Transformer Overload occurs in one of the distribution transformers at PT. PLN (Persero) UP3 South Makassar ULP Panakkukang, namely the GT.PTP001 Distribution transformator in Feeder Toddopuli with a loading amount of 84.43% exceeding the standard set by SLPN which is 80%. This study aims to find a way to overcome the problem of overload on the transformer GT.PTP001 in Feeder Toddopuli and also to get the load on the distribution transformer GT.PTP001 before and after Uprating the Transformer. Making this research using data collection method by taking data at ULP Panakkukang. Field supervisor interviews and literature studies that support problem solving on the GT.PTP001 transformer. Therefore, in overcoming the problem of overloading the GT.PTP001 transformer, improvements are made by looking at these conditions, one of which is by upgrading the transformer or adding a transformer with a larger capacity to 200 kVA from the previous 160 kVA. From the uprating results, the loading results obtained obtained the percentage value of transformer loading before uprating the transformer, namely 84.43% and after uprating the transformer, namely 68.18%, so that it decreased by 16.25%, which means that uprating the transformer is one of the methods that commonly used to overcome overload.